Pelaksanaan Layanan Konseling dan Tes HIV Sukarela di Puskesmas Kedungmundu Kota Semarang - Ritkha Aulia Fulansari; Septo Pawelas Arso; Wulan Kusumastuti (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Voluntary HIV counseling and testing services are an "entrance gate" for HIV control to achieve Indonesia's target of ending HIV AIDS by 2030. However, in 2020 due to COVID-19, most of the number of visits to voluntary HIV counseling and testing services in Semarang City has decreased, including at the Kedungmundu Health Center. The purpose of this study was to analyze the implementation of voluntary HIV testing and counseling services at the Kedungmundu Health Center. This study used a qualitative approach. Data were obtained from selected informants using purposive sampling technique. Data was collected through interviews, observations, and documentation studies. The results showed that the increasing number of voluntary HIV testing and counseling services at the Kedungmundu Health Center was motivated by several aspects including: the quality and quantity of staff, staff motivation and attitude, adequate budget, ease of service time, staff service schedule, clear information or directions and consistency, understanding of measures and objectives, services in accordance with SOPs, good coordination, monitoring, evaluation and coaching, good recording and reporting, support from non-governmental organizations, government support, and community support. It was concluded that the multifactorial background to the use of voluntary HIV testing and counseling services at the Kedungmundu Health Center, Semarang City, had been explored.Keywords: policy implementation; voluntary HIV counseling and testing; community health center ABSTRAK Layanan konseling dan tes HIV sukarela merupakan “pintu masuk” bagi pengendalian HIV untuk mencapai target Indonesia mengakhiri HIV AIDS pada tahun 2030. Namun, pada tahun 2020 akibat COVID-19, sebagian besar jumlah kunjungan layanan konseling dan tes HIV sukarela di Kota Semarang mengalami penurunan, termasuk di Puskesmas Kedungmundu. Tujuan penelitian ini adalah menganalisis pelaksanaan layanan konseling dan tes HIV sukarela di Puskesmas Kedungmundu. Penelitian ini menggunakan pendekatan kualitatif. Data diperoleh dari para informan yang dipilih dengan teknik purposive sampling. Data dikumpulkan melalui wawancara, pengamatan, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa meningkatnya jumlah pemanfaatan layanan konseling dan tes HIV sukarela di Puskesmas Kedungmundu dilatarbelakangi oleh beberapa aspek meliputi: kualitas dan kuantitas petugas, motivasi dan sikap petugas, anggaran yang memadai, kemudahan waktu layanan, jadwal pelayanan petugas, informasi atau arahan yang jelas dan konsisten, pemahaman tentang ukuran dan tujuan, pelayanan yang sesuai dengan SOP, koordinasi yang baik, adanya monitoring, evaluasi serta pembinaan, pencatatan dan pelaporan yang baik, dukungan lembaga swadaya masyarakat, dukungan pemerintah, serta dukungan masyarakat. Dsismpulkan bahwa telah tergali multifaktor yang melatarbelakangi pemanfaatan layanan konseling dan tes HIV sukarela di Puskesmas Kedungmundu, Kota Semarang.        Kata kunci: implementasi kebijakan; konseling dan tes HIV sukarela; pusat kesehatan masyarakat